Choice Behavior in Transition: Development of Preference With Ratio and Interval Schedules - Mazur, J.E. (Journal of Experimental Psychology: Animal Behavior Processes, 1992)
In Experiment 1, the choice responses of 8 pigeons were observed during 50 periods of transition. Each condition began with equal probabilities of reinforcement on 2 response keys and switched to unequal probabilities. With the ratio of the 2 probabilities held constant, preference for the higher probability developed more rapidly when the 2 probabilities were high than when they were low. In Experiment 2, each condition began with 2 equal variable-interval schedules, but later 1 key delivered 60%, 75%, or 90% of the reinforcers. The rate of approach to asymptotic performance was roughly the same with all 3 reinforcement percentages. These and previous results pose difficulties for some well-known models of acquisition, but the results are well described by a simple model that states that the strength of each response is independently increased by reinforcement and decreased by nonreinforcement.
30 citations (Crossref) [2023-10-31]
Keywords: Animal; Attention; Choice Behavior; Color Perception; Motivation; Orientation; Pigeons; Probability Learning; Problem Solving; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; animal; article; attention; color vision; decision making; dept.psy; learning; motivation; orientation; pigeon; problem solving; reinforcement

Choice with delayed and probabilistic reinforcers: effects of variability, time between trials, and conditioned reinforcers - Mazur, James E; Romano, Angela (Journal of the Experimental Analysis of Behavior, 1992)
In a discrete-trials procedure with pigeons, a response on a green key led to a 4-s delay (during which green houselights were lit) and then a reinforcer might or might not be delivered. A response on a red key led to a delay of adjustable duration (during which red houselights were lit) and then a certain reinforcer. The delay was adjusted so as to estimate an indifference point-a duration for which the two alternatives were equally preferred. Once the green key was chosen, a subject had to continue to respond on the green key until a reinforcer was delivered. Each response on the green key, plus the 4-s delay that followed every response, was called one “link” of the green-key schedule. Subjects showed much greater preference for the green key when the number of links before reinforcement was variable (averaging four) than when it was fixed (always exactly four). These findings are consistent with the view that probabilistic reinforcers are analogous to reinforcers delivered after variable delays. When successive links were separated by 4-s or 8-s “interlink intervals” with white houselights, preference for the probabilistic alternative decreased somewhat for 2 subjects but was unaffected for the other 2 subjects. When the interlink intervals had the same green houselights that were present during the 4-s delays, preference for the green key decreased substantially for all subjects. These results provided mixed support for the view that preference for a probabilistic reinforcer is inversely related to the duration of conditioned reinforcers that precede the delivery of food.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/131-277-176-129-505 tex.type: [object Object]
Keywords: Animal; Behavior; Animal; Choice Behavior; Competitive Behavior; Conditioning; Operant; Female; Instinct; Male; Models; Psychological; Pigeons; Reinforcement (Psychology); Reinforcement Schedule; Spatial Behavior; Support; U.S. Gov't; P.H.S.; animal; animal behavior; article; behavior; choice; competitive behavior; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; drive; female; instrumental conditioning; key peck; male; model; pigeon; pigeons; probability of reinforcement; reinforcement